Assessment of the Impact of Airlines External Environmental Factors on the Probability of Bankruptcy Risks in the Context of the COVID-19 - Senkus, Kastytis; Kamarauskienė, Irma; Šedytė, Samanta (Buhalterinės apskaitos teorija ir praktika, 2022)
The paper analyses which external environmental factors had the greatest impact on the probability of airline bankruptcy risk in the pre-pandemic and pandemic periods. In view of the strengths and weaknesses of the models selected and presented, the Altman Z 'score model was chosen for the study. It has been modified by recalculating the coefficients for the model's weighted indicators. The investigation included environmental macroeconomic statistics and financial data of 49 airlines in the airline sector over the span of ten years (2011-2021). The correlation method has identified the severity of external factors in connection with bankruptcy risks during the pre-pandemic and pandemic timeframe and has established a correlation between fluctuations in the risk of bankruptcy of the airline sector and environmental factors. Based on the results obtained, conclusions were drawn on the link between external environmental factors and changes in the sector’s bankruptcy risk score in the context of the COVID-19 pandemic. The results of the comparative analysis method showed that the influence of environmental factors analysed in Europe, North America, South America, and Oceania differs due to the predominance of business culture in the region. Overall, however, legal factors had the biggest negative impact on the sector before the COVID-19 pandemic (2011-2018), while other factors (passengers, competitors, labour force, and creditors) were weakly correlated with the likelihood of bankruptcy risk. During the COVID-19 pandemic, the most positive relationship between creditors intensified.
Keywords: probability of bankruptcy risk; external factors; Covid-19; airlines